La “economía espiritual” en Antioquia. Las funciones de las capellanías entre los siglos XVII-XVIII (2013)
ABSTRACT: Through the check of affidavits from the colonial period, this work presents the development and the influence of the chaplaincies in Antioquia between 17th and 18th centuries. The chaplaincies were pious institutions that served the souls of its founders and benefited at family priests. From the afterlife beliefs, the chaplaincies had roles in education, income and credit, as part of an “economía espiritual” (spiritual economy), and they strengthed the political and family connections within the power. Furthermore, the chaplaincies contributed to economic growth in Antioquia, with the investment of its goods in profitable activities.